PERBEDAAN LAKI-LAKI DAN PEREMPUAN DALAM AL-QUR'AN: TAFSIR QS. ALI IMRON AYAT 36 DARI PERSPEKTIF GENDER - . Mustofa (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2022)
This paper examines the interpretation of the Qur’an about the differences between men and women in the Qur’an from a gender perspective. Especially what is stated in the letter Ali Imran verse 36, using the tahlili method by using gender as a tools of analysis to analyze the interpretation of the Qur’an which textually mentions the differences between men and women. The goal is to understand what the meaning of the verses is. This paper is a literature review, by examining several books of interpretation which are still an important reference in Indonesia, either as books of educational teachings materials in Pesantren or books of interpretation which are references for scientific works. The result of this study indicate that the verse still has harmony with the concept of gender which means that men and women have equality in carrying out any activity, especially in worship. It can even be understood from the story of Sayyidah Maryam, which in essence she is no different from the chosen men who are equally allowed to guard Baitul Maqdis. Therefore, the Qur’an has given an encouragement to all Muslims to increase their deeds of worships without discriminating against gender.